1991
DOI: 10.1210/endo-128-4-1895
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Serum Levels Show a Midembryogenesis Peak in Chicken That Is Absent in Growth-Retarded Embryos Culturedex Ovo*

Abstract: Insulin-like growth factor-I (IGF-I) is the primary mediator of GH action after birth, but its role as a regulator of prenatal growth is unclear. In a previous study we showed that IGF-I mRNA was expressed in chicken embryos beginning at the blastoderm stage (day 0, newly laid egg). Here we present the ontogeny of serum IGF-I in normal and growth-retarded chicken embryos. Serum samples were pooled from multiple embryos starting on day 4 of development in ovo until hatching (day 21). Extracts of day 2 and 3 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The higher IGF-II concentrations observed in our study most likely reflect differences in the RIA reagents utilized in the respective assays. The pattern of circulating IGF-I in the chick embryo in our experiment was similar to that previously reported (Robcis et al 1991). In addition, no mid-incubation peak in plasma IGF-II was observed, unlike circulating IGF-I (Robcis et al 1991).…”
Section: Discussionsupporting
confidence: 90%
“…The higher IGF-II concentrations observed in our study most likely reflect differences in the RIA reagents utilized in the respective assays. The pattern of circulating IGF-I in the chick embryo in our experiment was similar to that previously reported (Robcis et al 1991). In addition, no mid-incubation peak in plasma IGF-II was observed, unlike circulating IGF-I (Robcis et al 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Plasma concentrations vary with the physiological age and state of the bird. Robcis et al (1991) have reported that circulating IGF-I levels peak in mid-incubation in the chicken embryo, and that the peak is absent in embryos incubated without shells. We noted a similar mid-incubation peak in circu¬ lating IGF-I in the developing turkey embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies conducted at our laboratory on in ovo feeding of amino acids and vitamins had significantly higher cGH expression (Bhanja, S.K., personal communication), Thus suggesting the role of in ovo feeding of nutrients for enhancing overall growth and proliferation of tissues in neonatal chicks. IGF‐I levels increased steadily during incubation from day 6 to peak at day 15 of incubation but reduced during hatch (Robcis et al., ). In the present study also, the expression of hepatic IGF‐1 gene was apparently higher on the 18th day of incubation and showed a decreasing trend towards hatch.…”
Section: Discussionmentioning
confidence: 99%